2018
DOI: 10.5946/ce.2017.114
|View full text |Cite
|
Sign up to set email alerts
|

Primary Colonic Follicular Lymphoma Presenting as Four Diminutive Sessile Polyps Found Incidentally During Colonoscopy

Abstract: Follicular lymphomas, which typically arise in the lymph nodes with spleen, liver, and bone marrow involvement, have generally low occurrence rates in Asian countries as compared with Western countries. Follicular lymphomas of the gastrointestinal tract are rare, and primary colonic follicular lymphomas are particularly rare compared with others found in the small intestine and duodenum. Colonoscopic imaging of colonic lymphomas, including follicular lymphoma, may reveal mucosal ulcerations, erosions, indurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The median age was 65.8 (range: 56-75) years old, and the male-to-female ratio was 4:4. According to the Lugano classification, the ratio of clinical stages I:II1 was 6: 2 and the endoscopic appearances of papular, polypoid and flat elevated type were observed in 4, 2 and 2cases, respectively (7)(8)(9)(10)(11)(12)(13)(14), and all of which showed raised lesions (Table). Nakamura et al reported that the endoscopic features of intestinal lymphoma may be classified as polypoid, ulcerative, multiple lymphomatous polyposis (MLP), diffuse, and mixed type (15).…”
Section: Discussionmentioning
confidence: 99%
“…The median age was 65.8 (range: 56-75) years old, and the male-to-female ratio was 4:4. According to the Lugano classification, the ratio of clinical stages I:II1 was 6: 2 and the endoscopic appearances of papular, polypoid and flat elevated type were observed in 4, 2 and 2cases, respectively (7)(8)(9)(10)(11)(12)(13)(14), and all of which showed raised lesions (Table). Nakamura et al reported that the endoscopic features of intestinal lymphoma may be classified as polypoid, ulcerative, multiple lymphomatous polyposis (MLP), diffuse, and mixed type (15).…”
Section: Discussionmentioning
confidence: 99%